Pemeriksaan gula darah dan asam urat sebagai upaya peningkatan kesehatan masyarakat - Nuryati, Arum; Wuri Astuti, Dian; Nadifah, Fitri; Anwarudin, Anwarudin (IKIP SILIWANGI, 2025)
The blood sugar, uric acid and blood pressure screening activities carried out in RT 04 Tamanan Wetan aim to increase efforts to detect non-communicable diseases.Diabetes Mellitus can cause various complications, including macrovascular or microvascular. Diabetes Mellitus can also cause quite serious cardiovascular disorders if not treated immediately because it can increase hypertension and heart infarction. Uric acid has a close relationship with purine metabolism disorders that can trigger an increase in uric acid levels in the bloodThe stages of activities that will be carried out include participant registration, blood pressure measurement, and random blood sugar level measurement. Participants in this health check-up were 77 people. The results of this examination showed that participants with hypertension were 64.9%, Pre-Diabetes 5.2%, Diabetes 10.4%, and High Uric Acid Levels 22.1%. In conclusion,This free health check activity is very beneficial for the community as an effort to improve public health.Keywords :Non-Communicable Diseases, Health Check-up